Karel Čapek i „renesansa“ češke kriminalističke proze 1958 – 1969. - Matija Ivačić ([sic])
After an entire decade (1948-1957) of being strictly forbidden and anathematized, Czech crime fiction gained sway in the post-February literary life at the end of the fifties. There were several impulses that led to this occurrence: (1) fatigue of the constructive novel as a representative prose genre of the first half of the fifties, (2) the Moscow conference on Sci-Fi and crime fiction in July of 1958, and (3) a series of essays, Marsyas of the US, published in the beginning of 1958 by L. Dorůžka, F. Jungwirth and J.Škvorecký in Světová literatura revue. In addition to that, works of Czech literary classic writer Karel Čapek carried imense importance in the process of affirmation of crime fiction in the period 1958-1969, which can also be seen in the works of writers and literary critics of liberal (pro-western) orientation. This article analyzes Čapek's contribution to the “Rennaissance” of Czech crime fiction on two different levels. The first level is a review of connections between his book of essays Marsyas or On the sidelines of literature and essays by Dorůžka, Jungwirth and Škvorecky in Marsyas of the US. The second level aims to detect the Čapek motifs in crime fiction produced between1958 and 1969.